A Randomized Controlled Trial to Compare Analgesia and Functional Improvement After Continuous Neuroablative and Pulsed Neuromodulative Radiofrequency Treatment of the Genicular Nerves in Patients with Knee Osteoarthritis up to One Year After the Intervention. Issue 3 (12th November 2020) - Santana-Pineda, María M; Vanlinthout, Luc E; Santana-Ramírez, Samuel; Vanneste, Thibaut; Van Zundert, Jan; Novalbos-Ruiz, José Pedro
Abstract: Objectives: To compare the analgesic and functional outcomes of continuous neuroablative radiofrequency (CNARF) and pulsed neuromodulative radiofrequency (PNMRF) treatment of genicular nerves up to 1 year after the intervention and to identify predictors associated with a successful outcome (defined as an at least 50% reduction in the pre-interventional visual analog scale [VAS] rating) after genicular radiofrequency treatment. Design: A prospective randomized controlled trial. Setting: The Pain Department of the Jerez de la Frontera University Hospital, Cadíz, Spain, from January 2018 until May 2019. Subjects: Patients with grade 3–4 gonarthritis suffering from knee pain, with a VAS score ≥5 for >6 months. Methods: Eligible participants were randomly assigned to receive either CNARF or PNMRF of the superior medial, superior lateral, and inferior medial genicular nerves. The VAS and Western Ontario and McMaster Universities Osteoarthritis (WOMAC) scores were assessed before and at 1, 6, and 12 months after treatment. Medication use was quantified before and at 6 months after the intervention. Potential characteristics associated with the efficacy of radiofrequency intervention were explored by using multivariable statistical models. Results: A total of 188 participants were included. The magnitude and duration of beneficial effect and reduction in analgesic use were significantly greater in the CNARF group. Success at 6 months after radiofrequency treatment decreased with grade 4 gonarthritis; higher pre-interventional VAS score; and concomitant depression, anxiety disorder, and diabetes mellitus. Conclusions: Therapeutic efficacy and reduction in analgesic consumption were superior after CNARF. Treatment success at 6 months after radiofrequency intervention decreased with more severe gonarthritis; higher pre-interventional pain intensity; and concomitant depression, anxiety disorder, and diabetes mellitus.